1980
DOI: 10.1063/1.327309
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and transport properties of pure and carbon-doped divalent RE hexaboride single crystals

Abstract: Single crystals of pure and carbon-substituted divalent hexaborides EuB 6 and YbB 6 have been prepared by the Al flux method. Lattice parameters, density measurements, and microprobe analysis show that the single crystals are very close to stoichiometry, EuB 6 is ferromagnetic (Tc = 12.S K and ()p = IS K) while YbB 6 is diamagnetic. Resistivity and Hall effect measurements carried out over a wide temperature range show that both pure hexaborides are semiconductors with a small intrinsic gap. The carbon-substit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
52
0
2

Year Published

1991
1991
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 10 publications
10
52
0
2
Order By: Relevance
“…We first consider the case of YbB 6 where the RE element is divalent. It has been reported that although YbB 6 single crystals may show metallic behavior in resistivity measurements at low temperature, defect-free YbB 6 would behave as an intrinsic semiconductor with a finite energy gap between the 5d and 2p bands [48]. The metallic behavior of YbB 6 is then ascribed to the formation of impurity bands [48].…”
Section: Resultsmentioning
confidence: 99%
“…We first consider the case of YbB 6 where the RE element is divalent. It has been reported that although YbB 6 single crystals may show metallic behavior in resistivity measurements at low temperature, defect-free YbB 6 would behave as an intrinsic semiconductor with a finite energy gap between the 5d and 2p bands [48]. The metallic behavior of YbB 6 is then ascribed to the formation of impurity bands [48].…”
Section: Resultsmentioning
confidence: 99%
“…This correlated topological phase in YbB 6 has been proposed to be explainable by an adjustable correlation parameter (Hubbard-U ) and a band inversion between the d and p bands under a nonzero Coulomb interaction value [15]. Moreover, the rare-earth hexaborides can provide a platform to realize a rich variety of distinct electronic ground states such as ferromagnetic order in EuB 6 and superconductivity in LaB 6 (T c ∼ 0.5 K) [4,16,17].…”
Section: Pacs Numbersmentioning
confidence: 99%
“…Single crystal samples of CeB 6 and BaB 6 used in our measurements were grown in the Fisk lab at the University of California (Irvine) by the Al-flux method, which is detailed elsewhere [12,16]. Synchrotron-based ARPES measurements of the electronic structure were performed at the Beamlines 4.0.3 and 10.0.1 of the Advanced Light Source, Berkeley, CA equipped with high-efficiency Scienta R8000 electron analyzers and beamline I4 of MAX-LAB III, Lund, Sweden equipped with a SPECS Phoibos 100 anlyzer.…”
Section: Pacs Numbersmentioning
confidence: 99%
“…36 Experimental data, however, do not support these theoretical predictions. [26][27][28]37 . Recent ARPES experiments [26][27][28] show that Yb-4f states are located at ∼ -1 eV and -2.3 eV below E F , indicating that YbB 6 does not belong to the Kondo insulator paradigm.…”
Section: Electronic Structure Of Ybb6mentioning
confidence: 99%
“…Early transport measurements indicated that YbB 6 is a doped semiconductor 37 . Recent ARPES experiments [26][27][28] however find that the Yb-4f states lie ∼ 1 eV below the E F , suggesting a non-TKI phase, contradicting theoretical predictions.…”
Section: Introductionmentioning
confidence: 99%